An Analysis of Students’ Mastery of Machinery-Related Vocabulary at SMK TKM Purworejo - Adista Adista; Junaedi Setiyono; Abdul Ngafif (Varied Knowledge Journal, 2026)
Vocabulary knowledge plays a vital role in vocational education, particularly for mechanical engineering students who are required to understand both general English and specialized technical terminology. However, many vocational learners continue to experience difficulties in mastering machinery-related vocabulary due to limited exposure, instructional constraints, and the gap between everyday English and technical language. This study aims to examine the level of students’ mastery of machinery vocabulary at SMK TKM Purworejo, identify the challenges they encounter, and explore the learning strategies they employ to acquire technical terms effectively. This research adopted a descriptive qualitative design using purposive sampling. The participants were mechanical engineering students who had received instruction on machinery-related vocabulary in their English classes. Data were collected through classroom observations, pre-tests, and document analysis. The data were then analyzed using thematic analysis to identify emerging themes and patterns related to vocabulary acquisition. The findings indicate that most students have achieved an adequate level of mastery of basic machinery vocabulary, particularly concrete terms related to tools and equipment. Approximately 95% of the students obtained satisfactory scores on the pre-test, indicating that the quantitative pre-test results supported the qualitative findings regarding their basic vocabulary mastery. Students applied various learning strategies, including contextual learning, comparing English terms with their first language equivalents, peer discussion, structured note-taking, repetition, and the use of digital platforms. Despite these positive outcomes, challenges remain, such as limited English exposure outside the classroom, pronunciation difficulties, confusion between general and technical vocabulary, and limited ESP-based instructional materials. Therefore, contextualized ESP instruction and innovative teaching strategies are essential to support continuous vocabulary development and professional readiness.